Arraying institutional layers in federalism reforms: lessons from the German case. Issue 5 (19th October 2016) - Behnke, Nathalie; Kropp, Sabine
ABSTRACT: The introductory article to this Special Issue offers an analytical framework for investigating federal reforms. By looking through the lens of institutional theory, it provides an avenue for grasping the basic mechanisms which are at work in reform processes. It is argued that the German case which comprises three distinct reform steps stretching out over more than one decade represents an especially suitable example for understanding the general logics of federal reform. As a "prototype" of sequential, asynchronous reforms, it allows for generating theoretical insights beyond the findings of a single case study. The article reveals that layering, sequencing, and the linkage of different arenas are the most relevant aspects to be considered when examining federal reforms. Finally, it is established how the contributions to this Special Issue refer to the analytical categories worked out in this introduction.